VARIANTS OF EMOTION LEXICONS, ‘MARAH’ (ANGRY) AND ‘MALAS’ (LAZY) IN LANGKAWI ISLAND: A GEO-LINGUISTIC ANALYSIS - Junaini Kasdan; Harishon Radzi; Julaina Nopiah (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
In general, research in geographical dialects in Malaysia has uncovered dialect distribution based on lexical and phonological differences, which has been the basis of today’s geo-linguistic studies. This study investigated the emotion lexicon, ‘marah’ (angry) and ‘malas’ (lazy), in the dialect of Malay, Langkawi Island. Data were collected through fieldwork with 447 respondents of youth, adult, and senior citizens across social status or educational levels. The collected data were transcribed using phonetic symbols and coded with ArcGIS software for producing choropleth maps. The research aimed to identify the variants of emotion lexicons in their daily conversation. The study found 12 variants of ‘angry’ and 12 variants of ‘lazy.' By comparing the difference and distribution of each lexicon variant, mapping was successfully conducted using the choropleth technique. The study has also successfully applied Geographic Information System (GIS) to describe geographical factors that influence the formation and distribution of emotion lexicon variants in Langkawi island, which proves their close relation with geographical aspects in Langkawi.